RANCANG BANGUN REPEATER UNTUK KOMUNIKASI LORA - Azwar, Hamid (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
Not all situations allow for direct observation of the object being observed. This is due to several factors, such as distances that are too far or terrains that are too dangerous to reach, as well as weather and temperature conditions that are not supportive. Therefore, observation or measurement cannot always be done directly and continuously in these difficult-to-reach locations. To overcome these constraints, telemetry is used for long-distance measurement. However, telemetry requires an adequate transmission range. One efficient method for long-distance transmission is using Long Range (LoRa) technology, which has deficient power consumption. LoRa repeaters are required to forward data from the Node to the Gateway to extend the transmission range. In this study, a LoRa repeater was developed for LoRa communication using the LoRa TTGO ESP32 module. The results of this repeater development demonstrate its ability to forward sensor data from the node to the gateway with a range of up to 2.8 km and a data transmission delay of 0.7 seconds.